Constancy and change in the U.S. age distribution of crime: A test of the “invariance hypothesis” - Britt, Chester L. (Journal of quantitative criminology, 1992)
The recent controversy over the age relationship with criminal behavior can be traced to Hirschi and Gottfredson's ( Am. J. Sociol. 89 , 552–584, 1983) failure to define “invariance.” In this paper, I distinguish two types of invariance— parametric and mathematical form — that explains both the pattern of stability claimed by Hirschi and Gottfredson and the pattern of variability observed in more recent research. I then directly test for each type of invariance using age-specific arrest data for index offenses in the United States from 1952 to 1987. The results are largely consistent with recent research showing variability in the characteristics (i.e., parameters) of the age distribution of crime, but at the same time, the results provide evidence for a persistent, underlying mathematical form to the age distribution of crime, regardless of year or offense type.